2007
DOI: 10.2500/ajr.2007.21.2984
|View full text |Cite
|
Sign up to set email alerts
|

Site of Attachment of Inverted Papilloma Predicted by CT Findings of Osteitis

Abstract: In patients in whom osteitis is detectable on the preoperative CT scan, the site of origin of the IP can be predicted with a high degree of accuracy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 17 publications
4
57
0
1
Order By: Relevance
“…Hypervascularization within the origin site may cause bone growth (31), driven by bone morphogenetic protein 4 expressed by SIP cells (33) or cytokines released due to inflammation (34). Bhalla et al (34) found that the predictive value of osteitis was 95% via CT scan, and similar results were also reported by Yousuf et al (35). Lee et al (31) evaluated 55 lesions associated with focal hyperostosis using CT images and revealed that the location of hyperostosis coincided with the actual tumor attachment sites in 49 (89.1%) of all the lesions.…”
Section: Clinical Prevention For the Recurrence Of Sipsupporting
confidence: 71%
“…Hypervascularization within the origin site may cause bone growth (31), driven by bone morphogenetic protein 4 expressed by SIP cells (33) or cytokines released due to inflammation (34). Bhalla et al (34) found that the predictive value of osteitis was 95% via CT scan, and similar results were also reported by Yousuf et al (35). Lee et al (31) evaluated 55 lesions associated with focal hyperostosis using CT images and revealed that the location of hyperostosis coincided with the actual tumor attachment sites in 49 (89.1%) of all the lesions.…”
Section: Clinical Prevention For the Recurrence Of Sipsupporting
confidence: 71%
“…35 There is a high correlation between the origin of the inverted papilloma and the presence of focal hyperostosis on the pre-operative CT; this may facilitate pre-operative prediction of tumour origin. [35][36][37] Magnetic resonance imaging There is no signature MRI appearance for benign inverted papilloma. The main utility of MRI is in defining the extent of the lesion and differentiating inverted papilloma from inspissated mucus.…”
Section: Computed Tomographymentioning
confidence: 99%
“…Occasionally, they can enlarge, endangering vital structures. Here, steroids or interferon-2 have a role [50]. Later in life, smaller capillary, venous or cavernous hemangiomas can present, often with epistaxis.…”
Section: Hemangiomamentioning
confidence: 99%